Particle dynamics in a pseudo-2D spouted bed: Experiments and Euler–Lagrange simulations - Antunes, Gabriella Gonçalves Borges; Bück, Andreas; Mariano, Felipe Pamplona; Girardi, Anderson Gomes; Dos Santos, Dyrney Araujo (Chemical Engineering Journal, 2024)
This study is dedicated to a comprehensive examination of particle dynamics within a pseudo-2D spouted bed, employing a combination of experimental analysis and numerical simulations conducted with the Euler-Lagrange approach. To develop a robust CFD-DEM model for predicting particle dynamics in a pseudo-2D spouted bed, our proposed methodology includes the measurement of DEM parameters based on experimental data, a grid size independence test assessment, and an analysis of appropriate turbulent models and wall boundary conditions for the fluid phase. The effect of different operating conditions, e.g., particle mass and inlet air velocity, on the complex turbulent multiphase flow behavior is assessed. Additionally, we numerically investigated the frequency of collisions between particles and the temporal changes in collisional forces across various conditions. The experiments and numerical simulations provide valuable insights into the intricacies of particle dynamics within a pseudo-2D spouted bed, offering essential knowledge for the optimization of processes employing this equipment.
Keywords: CFD; Spouted bed; DEM; Multiphase flow collision